Characterising the Exposure of Prison Staff to Second-Hand Tobacco Smoke. Issue 7 (16th July 2017) - Semple, Sean; Sweeting, Helen; Demou, Evangelia; Logan, Greig; O'Donnell, Rachel; Hunt, Kate
Abstract: Second-hand tobacco smoke (SHS) is an avoidable and harmful exposure in the workplace but >25000 prison staff continue to be exposed on a daily basis in the UK and many more worldwide. SHS exposures in prisons are incompletely understood but may be considerable given the large proportion of smoking prisoners and limited ventilation. This study characterized the exposure of prison staff to SHS in all 15 prisons in Scotland using multiple methods. Exposure assessment strategies included 6-day area measurement of fine Particulate Matter (PM2.5 ) and airborne nicotine in each prison together with short (30-minute) measurements of PM2.5 covering a range of locations/activities. Pre- and post-shift saliva samples were also gathered from non-smoking staff and analysed for cotinine to estimate exposure. There was evidence of exposure to SHS in all prisons from the results of PM2.5 and nicotine measurements. The salivary cotinine results from a sub-sample of non-smoking workers indicated SHS exposures of similar magnitude to those provided by the 6-day area measurements of PM2.5 . There was a high degree of exposure variability with some locations/activities involving exposure to SHS concentrations that were comparable to those measured in bars in Scotland prior to smoke-free legislation in 2006. The median shift exposure to SHS-PM2.5 was ~20 to 30 µg m −3 and is broadly similar to that experienced by someone living in a typical smoking home in Scotland. This is the most comprehensive assessment of prison workers' exposure to SHS in the world. The results are highly relevant to the development of smoke-free policies in prisons and should be considered when deciding on the best approach to provide prison staff with a safe and healthy working environment.